JOB PERFORMANCE EVALUATION THROUGH AFFECTIVE COMMITMENT AND JUSTICE PERCEPTIONS - Derry Permata Sari; Hendra Lukito; Donard Games (Journal Publicuho, 2023)
Employee performance investigation from justice perception is a must in government sector, especially in HR Division, because it is associated with their job function which operates in employee management. This study aims to investigates the effect of interactional justice and procedural justice on job performance, and assess mediating contribution of affective commitment due to it describe emotional attachment of employee. Recorded sample was 48 and then the data analyst with Smart PLS version 4.0.9. Results stated that interactional and procedural justice have not significant effects on performance in the direct manner. Mediating contribution of affective commitment enhance the relationship interactional justice and performance by partial effect, while in the relationship between procedural justice on performance, affective commitment also has a partial contribution but not improve those relationship.